Details of the cooperative binding of piperlongumine with rat serum albumin obtained by spectroscopic and computational analyses - Povinelli, Ana Paula Ribeiro [UNESP]; Zazeri, Gabriel [UNESP]; de Freitas Lima, Marcelo [UNESP]; Cornélio, Marinônio Lopes [UNESP] (Springer Nature, 2019)
Piperlongumine (PPL) has presented a variety of important pharmacological activities. In recent pharmacokinetics studies in rats, this molecule reached 76.39% of bioavailability. Although PPL is present in the bloodstream, no information is found on the interaction between PPL and rat serum albumin (RSA), the most abundant protein with the function of transporting endo/exogenous molecules. In this sense, the present study elucidated the mechanism of interaction between PPL and RSA, using in conjunction spectroscopic and computational techniques. This paper shows the importance of applying inner filter correction over the entire fluorescence spectrum prior to any conclusion regarding changes in the polarity of the fluorophore microenvironment, also demonstrates the convergence of the results obtained from the treatment of fluorescence data using the area below the spectrum curve and the intensity in a single wavelength. Thermodynamic parameters revealed that PPL binds to RSA spontaneously (ΔG < 0) and the process is entropically driven. Interaction density function method (IDF) indicated that PPL accessed two cooperative sites in RSA, with moderate binding constants (2.3 × 105 M−1 and 1.3 × 105 M−1). The molecular docking described the microenvironment of the interaction sites, rich in apolar residues. The stability of the RSA-PPL complex was checked by molecular dynamics.